Improving Energy and Economic Efficiency in Dimethyl Ether Production through Heat Duty Reduction in a Two-Stage Methanol Dehydration Process - Nurdin, Faza Ryviansyah; Annisafitri, Hasnaa; Hasian, Jonathan; Muzaki, Risyad Prasetya; Towidjojo, Shafa Noviandrea (Journal of Chemical Engineering Research Progress, 2025)
This study investigates the optimization of a two-step dimethyl ether (DME) production process via methanol dehydration, with a focus on enhancing thermal and economic performance through strategic heat integration. A modified configuration was developed by redirecting residual heat from coolers to pump inlets and transferring thermal energy from the condenser of the secondary distillation column to the reboiler of the primary column. These internal heat recovery strategies significantly reduced external utility demand without compromising product purity or plant throughput. Simulation results demonstrate a reduction in total energy consumption from 4,466,363.8 kJ/h to 3,211,110 kJ/h, equivalent to a 31.03% decrease in thermal energy requirement. In parallel, the annual utility cost was reduced by 58.15%, and the annual operating cost decreased by 12.77%, yielding total savings of $407,304 per year. Importantly, the modified process maintained a DME purity exceeding 99% and preserved the original production capacity of 50,000 tons per year, confirming the feasibility of these improvements without compromising performance targets. Overall, the proposed retrofit offers a more energy-efficient and cost-effective pathway for industrial-scale DME production, serving as a model for sustainable process design in energy-intensive chemical systems. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).